2014
DOI: 10.3126/ijasbt.v2i4.11551
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fruit and Vegetable Losses at Major Wholesale Markets in Nepal

Abstract: A study regarding the losses of harvested horticultural produces in the major fruit and vegetable wholesale markets of Nepal was conducted to identify the major causes of fruits and vegetable wastage. This study aimed at generating useful information about the causes of loss of horticultural produce, types of loss and also about the possibility of reuse and recycling of such organic wastes as resource for composting and vermicomposting. Survey of the three major market centers namely; Narayangadh, Pokhara, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…From these observations, it is evident that the major factor causing the loss of the produce was the lack of storage facility followed by inappropriate packaging and poor handling of the produce, and finally poor quality of the produce. Our findings substantiate the report by Devkota et al (2014) who reported that lack of cold store and inappropriate packaging facility had significant effect on postharvest losses of fruit in Nepal. Similarly, Zenebe et al (2015) identified storage condition and transportation practice as important determinants for the postharvest loss of banana in Ethiopia.…”
Section: Causes Of Fruit Postharvest Losssupporting
confidence: 92%
See 1 more Smart Citation
“…From these observations, it is evident that the major factor causing the loss of the produce was the lack of storage facility followed by inappropriate packaging and poor handling of the produce, and finally poor quality of the produce. Our findings substantiate the report by Devkota et al (2014) who reported that lack of cold store and inappropriate packaging facility had significant effect on postharvest losses of fruit in Nepal. Similarly, Zenebe et al (2015) identified storage condition and transportation practice as important determinants for the postharvest loss of banana in Ethiopia.…”
Section: Causes Of Fruit Postharvest Losssupporting
confidence: 92%
“…Improper harvesting and postharvest handling practices result in loss due to spoilage of the produce before reaching to consumers along with the loss in quality of the produce such as deterioration in appearance, taste and nutritional value. The high perishable nature of fruit, lack of storage facilities, mechanical injuries due to improper handling, packaging, transportation, and microbial infection are the major reasons for postharvest loss in fruits (Devkota et al, 2014). Zenebe et al (2015) pointed out market distance, duration of transport, storage condition, storage duration, duration of ripening, ripening room types, means of transport, and experience in banana marketing as important determinants of the postharvest loss of banana in Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…The uncontrolled environmental condition cause rapid rate of transpiration and piling of the fruits cause the bruising damage. Devkota et al (2014) reported that 51% of the loss was due to rotting, 22 % was due to mechanical damage and 27% physiological loss during handling, marketing and transportation of fruits.…”
Section: Transportation Lossmentioning
confidence: 99%
“…Successful agribusiness entrepreneurship should be supported and promoted by the investment on basic infrastructures such as strong research and development systems, construction of irrigation channels, link roads, and power, marketing systems, storage facilities etc. Huge amounts of fruits and vegetables are wasted everyday due to the lack of proper post-harvest facilities at the fruit and vegetable wholesale markets (Devkota et al, 2014).…”
Section: Lack Of Infrastructure Facilitiesmentioning
confidence: 99%